Turnover of O&M of distributaries to farmers' organisations, Polonnaruwa District: final report - Consultants in Technology Management and Development Studies (International Irrigation Management Institute, 1992)
The study was concerned with the Rapid Rural Appraisal (RRA) sub-project of the Irrigation Systems Management Project (ISMP). The purpose of the study was to ensure that the program of turning over of management of Distributory Canals (DCs) to Farmers ' Organisations (FOs) under the ISMP is a learning process for the project. The study was sponsored by the research advisory committee of the ISMP with participation of IIMI as the coordinator.